Pengaruh Kualitas Layanan Terhadap Loyalitas Nasabah Bank Syariah - Didit Darmawan; Dila Istianah (Pelantar Press, 2026)
Islamic banks face many challenges in maintaining and enhancing customer loyalty amid a highly competitive banking industry. Service quality is one of the key factors determining customer loyalty toward Islamic banking products and services. This research provides an analysis of how service quality affects customer loyalty in Islamic financial institutions. This study adopts a qualitative descriptive methodology, drawing on existing literature to offer a comprehensive analysis of the impact of service quality on fostering customer loyalty at Islamic banks.. The data analysis results indicate that high-quality service positively and significantly influences loyal customers at Islamic banks. In this context, loyalty means that customers will continue to use the bank’s services, recommend them to others, and choose the Islamic bank as their preferred option. Satisfied customers will make a positive contribution to the bank in the long term by remaining customers of the Islamic bank and recommending others to use their services. As a result, high standars of service are directly linked to an increase in loyal behavior among customers